BISNIS ONLINE: PREFERENSI KONSUMEN TERHADAP LAYANAN ONLINE FOOD DELIVERY - Nadiah Arum Mindarti; Made Siti Sundari; Sugeng Hariadi (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
This research studies the factors that influence consumers in using online food delivery services. The variables used are Time Saving Orientation, Price Saving Orientation, and Behavior Intention to OFD Services. The questionnaire is used in the data collectionprocess. Questions in this study were published online and offline. Online distribution is done through Google Form and offline distribution is done by distributing it to students of the University of Surabaya. A total of 208 valid questionnaires were collected to besubmitted using Structural Equation Modeling (SEM) data processing with SmartPLS software. Time Saving Orientation and Price Saving Orientation have positive and significant effect on Behavior Intention Towards OFD Services which support t-statisticsof 3,562 & 3,272 and P-Values of 0,000. The more culinary entrepreneurs who use e-commerce, the more transactions will occur, so it will increase the GRDP which will ultimately increase economic growth.